2020
DOI: 10.1093/milmed/usaa178
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Surgical Simulator: A Temporal Bone Simulator Validation Study of the Stryker Surgical Simulator (S3)

Abstract: Introduction The Stryker Surgical Simulator is a hybrid, temporal bone simulator that uses both tactile and haptic feedback combined with a computer interface. We sought to validate this simulator as an otolaryngology resident training tool for performing tympanomastoidectomy. Materials and Methods 15 residents and staff performed five basic cortical mastoidectomies. Staff surgeons comprised the “expert” cohort and resident s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
2
0
5
Order By: Relevance
“…Meyer et al compared the drilling performance of a bone simulator with a haptic system between the trainee resident group and the expert staff surgeon group. They concluded that there were no significant differences in surgical time or the accuracy of the surgical technique 13 . Thus, the use of a spine surgery simulator with a haptic system may be useful for spine surgery education, which has a steep learning curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meyer et al compared the drilling performance of a bone simulator with a haptic system between the trainee resident group and the expert staff surgeon group. They concluded that there were no significant differences in surgical time or the accuracy of the surgical technique 13 . Thus, the use of a spine surgery simulator with a haptic system may be useful for spine surgery education, which has a steep learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous reports described the availability of haptic technology for surgical simulators [12][13][14] . Meyer et al compared the drilling performance of a bone simulator with a haptic system between the trainee resident group and the expert staff surgeon group.…”
Section: Discussionmentioning
confidence: 99%
“…Os protocolo MiSSES, com questões adaptadas de outros estudos de validação de osso temporal 3D e criações 3D com foco em otorrinolaringologia [6,7,15,30,39,41,42] , com participação e anuência na sua construção de Deborah M.…”
Section: Seleção Dos Avaliadores Externosunclassified
“…A maioria dos participantes afirmou que os ossos temporais impressos em 3D devem ser incorporados ao currículo de treinamento de dissecção óssea temporal e que eles recomendariam o modelo de osso temporal impresso em 3D para outros estagiários. Nossos resultados sugerem o já discriminado em outros estudos, em que se evidencia que o modelo do osso temporal impresso em 3D é um treinamento valioso ferramenta de aprendizagem de procedimentos otológicos [6,15] .…”
Section: Reações Geraisunclassified
See 1 more Smart Citation